Pomen odprtega javnega prostora v središčih majhnih mest z vidika izvajanja storitev splošnega pomena - Volgemut, Mateja (Annales. Series historia et sociologia, 2021)
The article deals with the physical appearance, meaning and function of open public space (OPS) in the context of services of general interest (SGI) and its impact on the quality of life of inhabitants of small towns in Slovenia. Special emphasis is placed on the working hypothesis that, the OPS in interaction with SGI provide a higher quality of living while simultaneously helping to shape and promote the urban development of small towns. In the study, the cartographic method and the questionnaire were used, and the synthesis of both parts of the study was used, which additionally confirmed the working hypothesis. The results showed that cities are equipped with OPS in very different ways; they also differ in the physical appearance and function of the OPS, which impacts the satisfaction of living in the city. The frequency of their use is influenced by the design of the city centre, the arrangement of OPS and the provision of SGIs. The method of OPS research in interaction with SGI is suitable for further study of cities also from the point of view of urban governance and the urban economy, which will contribute to the decision-making on the OPS regulation to improve the attractiveness of the city centre and increase the supply and modernise SGI.
Keywords: centres of small towns; function of open public space; javne službe; javne storitve; javni prostor; kvaliteta življenja; majhna mesta; quality of living; services of general interest; Slovenia; Slovenija